Adsorptive desulfurization of heavy naphthenic oil: Equilibrium and kinetic studies. (23rd November 2017) - Moreira, A.M.; Brandão, H.L.; Hackbarth, F.V.; Maass, D.; Ulson de Souza, A.A.; Guelli U. de Souza, S.M.A.
Graphical abstract: Highlights: Selective organosulfur compounds removal from synthetic and real naphthenic oils. The effect of coexisting inhibitors on the adsorption performance was investigated. Carbon activated adsorptive desulfurization capacity was studied. Water, carbazole, naphthalene and phenol strongly inhibited sulfur adsorption. Abstract: Models of adsorptive desulfurization to remove the major refractory sulfur compounds, such as thiophene (T), benzothiophene (BT) and dibenzothiophene (DBT) in decahydronaphthalene (DHN), were investigated. The experimental desulfurization of naphthenic oils using activated carbon was conducted in an adsorption system at different temperatures. The adsorptive capacity and selectivity of the adsorbent for sulfur compounds and the effects of coexisting inhibitors on the adsorption performance were examined. The activated carbon showed high capacity and selectivity in the adsorptive desulfurization of naphthenic oil. Water, carbazole, naphthalene and phenol in synthetic naphthenic oil have a strong inhibiting effect on the desulfurization performance of the adsorbent at 100 °C. Increasing the temperature to 150 °C can significantly improve the performance of the adsorbent in the desulfurization of real naphthenic oils. The results showed that the activated carbon exhibited a remarkable adsorption performance. The adsorption capacities reached 1.6 × 10 −2, 2.0 × 10 −2 and 1.9 × 10 −2  kg kg −1 for T, BT and DBT in DHN, respectively. The Langmuir-Freundlich and Toth isotherm models provided good fits with the experimental equilibrium data for the real naphthenic oils. The kinetic results for the real naphthenic oils showed that the adsorption process can be described by a second-order mass transfer model. The results revealed that a temperature increase favors the sulfur adsorption kinetics and there was a greater diffusivity resistance for heavier oils. The data obtained showed effective diffusivity coefficients of between 7.5 × 10 −15 and 2.6 × 10 −13  m 2  s −1 and mass transfer coefficients for the external fluid film ranging from 8.3 × 10 −8 to 4.9 × 10 −7  m s −1 .